Peran Kepemimpinan dan Komunikasi dalam Manajemen Filantropi: Analisis Terhadap Implementasi Program Bantuan Sosial - Yudo Zulkarnain; Mujiyati (Pawarta: Journal of Communication and Da'wah, 2024)
Philanthropy management and social assistance programs play essential roles in improving community welfare. In this context, this article examines the roles of leadership and communication in implementing social assistance programs. Through a review of relevant literature and related research, it is found that effective leadership and transparent communication are crucial for the success of social assistance programs. The study also identifies several key factors, including communication effectiveness, community participation, and beneficiary satisfaction, as essential to achieving program goals and generating significant social impact. Additionally, the discussion encompasses aspects such as program implementation efficiency, diversification of the program, and geographical considerations. By applying results from relevant literature, philanthropic organizations can enhance their strategies and practices in designing and implementing more effective and impactful social assistance programs.